La mujer en la prensa semanal de Pamplona de principios de siglo - Elso Areta, María Puy (Huarte de San Juan. Geografía e Historia, 1998)
This article tries to broach the subject of women in Pamplona at the beginning of the twentieth century. To reach the objective of the article, use has been made only of press publications in Pamplona that correspond to the time period studied. The investigation shows news edited by the above-mentioned publications that contain topics related to the feminine "environment". The first, and clearest, conclusion to be arrived ad from this study is the confirmation of the shortage of news and information relative to women. Although the press deal with various subjects such as education, incorporation into the employment market, appearance in politics and, to a lesser extent, prostitution etc. There is one subject that is dealt with in all publications, except "Porvenir Navarro" — Navarra Future. This subject is that of feminine moral values. The idea of considering women as campaigners transmitting traditional moral values causes this subject to be present in the majority of the articles published about women from Pamplona at the beginning of the century.